A quality improvement project for delirium prevention and management over the Greater Manchester Critical Care Network. (May 2021) - Davis, Jessica; Berry, Karen; McIntyre, Rebecca; Conway, Daniel; Thomas, Anthony; Hanison, James
Background: Delirium is a common complication of critical illness with a significant impact on patient morbidity and mortality. The Greater Manchester Critical Care Network established the Delirium Reduction Working Group in 2015. This article describes a region-wide delirium improvement project launched by that group. Methods: Multiple Plan-Do-Study-Act cycles were undertaken. Cycle 1: April 2015 demonstrated only 48% of patients had a formal delirium screen. Following this a network-wide event took place and the Delirium Standards for the Greater Manchester Critical Care Network were produced. Cycle 2: May 2016 quarterly audits across the network monitored compliance against the agreed standards. Group events involved implementation of a delirium care bundle, sharing best practice, educating staff and providing guidance on the management of delirium. Cycle 3: November 2016 quarterly audit continued and a regional delirium study day was rolled out across the region. Results: We have 14 different units across our network, all of which have participated in the audit. The first audit showed a delirium point prevalence of 28%, subsequent point prevalence audits demonstrated rates as low as 13%. There has also been an improvement in the use of delirium screening tools. In the first audit 37% of patients had two delirium screens in 24 h, this has increased to 60% in the latest audit. Improvements were also made in availability of sensory aids and pain assessments. Conclusion: The project has demonstrated the feasibility of delivering a coordinated delirium improvement project across multiple critical care units.